Optimisation of Mycobacterium bovis BCG Fermentation and Storage Survival - Jordan Pascoe; Charlotte L. Hendon-Dunn; Colin P.D. Birch; Gareth A. Williams; Mark A. Chambers; Joanna Bacon (MDPI AG, 2020)
Mycobacterium bovis Bacillus Calmette-Guérin (M. bovis BCG) was generated over a century ago for protection against Mycobacterium tuberculosis (Mtb) and is one the oldest vaccines still in use. The BCG vaccine is currently produced using a pellicle growth method, which is a complex and lengthy process that has been challenging to standardise. Fermentation for BCG vaccine production would reduce the complexity associated with pellicle growth and increase batch to batch reproducibility. This more standardised growth lends itself to quantification of the total number of bacilli in the BCG vaccine by alternative approaches, such as flow cytometry, which can also provide information about the metabolic status of the bacterial population. The aim of the work reported here was to determine which batch fermentation conditions and storage conditions give the most favourable outcomes in terms of the yield and stability of live M. bovis BCG Danish bacilli. We compared different media and assessed growth over time in culture, using total viable counts, total bacterial counts, and turbidity throughout culture. We applied fluorescent viability dyes and flow cytometry to measure real-time within-culture viability. Culture samples were stored in different cryoprotectants at different temperatures to assess the effect of these combined conditions on bacterial titres. Roisin's minimal medium and Middlebrook 7H9 medium gave comparable, high titres in fermenters. Flow cytometry proved to be a useful tool for enumeration of total bacterial counts and in the assessment of within-culture cell viability and cell death. Of the cryoprotectants evaluated, 5% (v/v) DMSO showed the most significant positive effect on survival and reduced the negative effects of low temperature storage on M. bovis BCG Danish viability. In conclusion, we have shown a reproducible, more standardised approach for the production, evaluation, and storage of high titre, viable, BCG vaccine.